A influência da televisão nos debates de sala de aula: uma análise com base na hipótese de Agenda-Setting - Silva, Evangicléia Sousa da (2015)
The media, particularly television, has been the subject of numerous academic studies. In this sense, we sought to verify the influence of media content in the perception of high school students Meta College in Goiania, based in Agenda-Setting hypothesis. That dissertation did a content analysis of essays prepared by students on the demonstrations that took place in June 2013 in the main capitals of Brazil, and in a complementary way, it was examined whether there is use of media content in the classroom through observation simple and interview with the school coordinator. The corpus of this research is focused on the proposed schedule by the authors: Maxwell McCombs and Donald Shaw (1972), and later studied by researchers such as: Mauro Wolf, Nelson Teasing, among others. Therefore, we studied the extent to which the media influence and schedule the perception of the said school students in relation to the 2013 protests.